Preparing for the next winter: Europe's gas outlook for 2023 - Ben McWilliams; Simone Tagliapietra; Georg Zachmann; Thierry Deschuyteneer (Bruegel, 2023)
The European Union has so far weathered the energy crisis brought on by Russia's invasion of Ukraine in February 2022 and will manage winter 2022/23 even if Russia abruptly halts all pipeline gas flows. However, preparations must be made for winter 2023-24. In particular, gas storage facilities should be 90 percent full by 1 October 2023. We assess the demand reduction needed if the 90 percent storage target is to be achieved. Our assessment takes into account EU imports, exports to refill gas storage facilities in Ukraine and Moldova, the weather and the situation in power markets, where gas demand is highly dependent on non-gas energy sources. Assuming limited Russian exports continue, and weather conditions are typical, demand up to 1 October 2023 must remain 13 percent lower than the previous five-year average. The EU should therefore extend its demand- reduction target, which is currently set to expire on 31 March 2023. Two variables will determine how easily the target can be met: 1) liquified natural gas (LNG) supply, and 2) the nature of demand reductions. Plans for rapid deployment of regasification units will alleviate concerns over LNG import infrastructure capacity. However, the EU will continue to compete internationally for LNG cargoes, and will remain vulnerable to global dynamics. Strong economic growth in China, for example, could further tighten markets. The way demand is reduced will determine the economic consequences. So far, large reductions in industrial gas demand have not been accompanied by dramatic drops in industrial output, suggesting good substitution options. However, hardly any gas was saved in the power sector last year, because of weak nuclear and hydro output. The return of French nuclear output will therefore be a huge positive. Finally, households have reduced gas demand, partly driven by warmer than usual weather. Record numbers of heat pumps were deployed in 2022, suggesting the start of a structural shift away from gas demand for heating. Policy should support a continued structural shift away from gas. This involves enabling rapid deployment of renewables and the accompanying grid infrastructure, energy-efficiency measures, help for households that want to switch to cleaner heating, and collaboration with industry to accelerate adoption of new low-carbon production methods.
Keywords: 330